ANALISIS KENAIKAN PANGKAT DAN JABATAN DOSEN POLITEKNIK KESEHATAN - Ni Nyoman Kasihani (Politeknik Kesehatan Kemenkes Mamuju, 2017)
Lecturer is one of the most important components in the organization of higher education. Promotion and position is a trust and appreciation given to the lecturer for the achievements that have been achieved. Obtain information of factors related to promotion and position of lecturer at Health Polytechnic of Ministry of Health. Cross Sectional method research in June-October 2017. Data collected using Likert Scale Questionnaire. The research was conducted on permanent lecturer of Health Polytechnic of Kemenkes Jakarta I who has functional position of 60 people. Sample amounted to 47 people (response rate 78.33%). Data were processed and analyzed univariate, bivariate and multivariate. Lecturers characteristic variable has no significant correlation with promotion and position of lecturer with p value > 0,05. Components of PAK that have significant relationship with promotion and lecturers position are education and teaching variables with p value 0,024 and value of OR 19,808 and research variable with p value 0,007 value OR 40,798. The variable of community service and supporting activities is not significant with p value > 0,05. PAK management system has a significant with p value 0,004 value OR 19,918. Significant variable on promotion and position of lecturers is education and teaching, research and management system of PAK. The variable that has the greatest relationship with promotion and position of lecturer is research. An intensive training for lecturers is required for the publication of scientific papers in national and international journals and to reward lecturers who publish scientific works to improve motivation to work.